P‐231: Late‐News Poster: Mechanical Behavior Study of Flexible Material. Issue 1 (May 2017) - Chang, Cheng-Hao; Wang, Wen-Ting; Hsieh, Wei-Jung; Wang, Wan-Tsang; Lin, Yu-Hsin
Abstract : Bendability is a key feature to define robustness of the flexible material. In order to quantify the bendability, there are many different mechanisms for bending test. Although those bending test machines may do the same bending radius, frequency and so on, however, the mechanism with and without the supporting plate induced different mechanical behavior. In this paper, the influence between the designs of mechanism and the stress trend has been disclosed.